2005
DOI: 10.1681/asn.2004070584
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Embryonic Stem Cells in Metanephric Kidney Organ Culture

Abstract: Many stages of nephrogenesis can be studied using cultured embryonic kidneys, but there is no efficient technique available to readily knockdown or overexpress transgenes for rapid evaluation of resulting phenotypes. Embryonic stem (ES) cells have unlimited developmental potential and can be manipulated at the molecular genetic level by a variety of methods. The aim of this study was to determine if ES cells could respond to developmental signals within the mouse embryonic day 12 to embryonic day 13 (E12 to E1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 36 publications
(28 reference statements)
0
67
1
2
Order By: Relevance
“…29 Also, ES cells have been transplanted in to murine day 12 and 13 embryos amid the metanephric mesenchyme, and these cells have integrated into the metanephric kidney in the organ culture. 30 ECM proteins have been shown to direct ES cell differentiation and are factors affecting cell behavior during organogenesis. 22,[31][32][33][34][35] Furthermore, differentiation toward a target tissue is improved if the ECM protein architecture closely resembles the in vivo ECM of the targeted tissue.…”
Section: Discussionmentioning
confidence: 99%
“…29 Also, ES cells have been transplanted in to murine day 12 and 13 embryos amid the metanephric mesenchyme, and these cells have integrated into the metanephric kidney in the organ culture. 30 ECM proteins have been shown to direct ES cell differentiation and are factors affecting cell behavior during organogenesis. 22,[31][32][33][34][35] Furthermore, differentiation toward a target tissue is improved if the ECM protein architecture closely resembles the in vivo ECM of the targeted tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al (72) used this approach to provide evidence that murine ES cells had the potential to give rise to mesonephric ducts and UB in teratomas. In contrast, Steenhard et al (73) reported 50% integration of undifferentiated ES cells into the tubules of embryonic kidneys without evidence for teratomas. Kobayashi et al (74) created Wnt4-transformed murine ES cells and showed in vitro that these had the capacity to form aquaporin 2-positive renal tubules.…”
Section: Human Es Cellsmentioning
confidence: 92%
“…With respect to technical risks, in vivo injection of these pluripotent cells can give rise to teratomas, as demonstrated by Yamamoto et al [57], who reported the generation of teratomas containing metanephric-mesenchyme-related structures after injection of undifferentiated ES cells within the peritoneum of nude mice [57]. In contrast, Steenhard et al [58] reported a 50% integration of undifferentiated ES cells into the tubules of embryonic kidneys without evidence of teratoma formation. The directed differentiation of ES cells to a renal progenitor fate has been performed by priming embryonic bodies (EBs) with retinoic acid, acitivin-A and BMP7 [59].…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%